Zurich Cementless Dual Mobility Cup for Canine Total Hip Prosthesis: Implant Characteristics and Surgical Outcome in 105 Cases - Lanz, Otto I.; Forzisi, Ida; Vezzoni, Aldo (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Dislocation after total hip arthroplasty (THA) remains a troublesome complication, and a source of frustration for the owner and the surgeon. The dislocation rate of hip prostheses in dogs is reported to range from 4 to 15%, representing the most common short-term complication. This is especially true in large and giant breed dogs, usually requiring revision surgery. With the increase in the number of THA being performed in veterinary surgery, reducing or preventing complications such as postoperative THA dislocation will be of paramount importance. The Zurich cementless dual mobility (DM) system allows impingement-free range of angulation of 80 to 132 degrees between the ceramic head and the polyether ether ketone (PEEK) cup when combined with the range of the PEEK cup in the outer metal cup. In this article, we review the use of the DM cup in THA in large and giant breed dogs, in terms of its history, biomechanics, outcomes and complications based on 105 cases.
Keywords: hip arthroplasty; dual mobility cup; cementless; dog; dislocation